Gene therapy for ADA‐SCID, the first marketing approval of an ex vivo gene therapy in Europe: paving the road for the next generation of advanced therapy medicinal products. Issue 6 (10th April 2017) - Aiuti, Alessandro; Roncarolo, Maria Grazia; Naldini, Luigi
Abstract : Gene and cell therapy research recently reached a fundamental milestone toward the goal to deliver new medicines for orphan diseases. In 2016, the European Commission granted market approval to GlaxoSmithKline (GSK) for ex vivo hematopoietic stem cell (HSC) gene therapy for the treatment of adenosine deaminase (ADA)‐deficient severe combined immunodeficiency (SCID), a very rare congenital disorder of the immune system. The new medicine, named Strimvelis™, is an advanced therapy medicinal product (ATMP) (Salmikangas et al, 2015 ) originally developed by the San Raffaele Telethon Institute for Gene Therapy (SR‐Tiget), a joint venture between Telethon Foundation and San Raffaele Scientific Institute. This ATMP is the first ex vivo stem cell gene therapy to receive regulatory approval anywhere in the world. Strimvelis™ consists of a single infusion of autologous gene‐corrected HSC and is prepared from the patient's own bone marrow (BM) HSCs, which are genetically modified using a gamma‐retroviral vector to insert a functional copy of the ADA gene. Abstract : An engaging account of the long road to approval of the first ever ex‐vivo stem cell gene therapy to receive regulatory approval, Strimvelis™, indicated for the treatment of ADA‐deficient severe combined immunodeficiency (SCID).